The Influence Of Accounting Information Systems, Peer To Peer Lending (P2P), And Payment Gateways On The Financial Performance Of Msmes In Surabaya City - Aulia Nur Rachmani; Merlayana Dwinda Yanthi (Majapahit Journal of Islamic Finance and Management, 2026)
The aim of this study is to investigate the impact of accounting information systems, peer-to-peer (P2P) lending, and payment gateways on the financial performance of MSMEs in Surabaya. The study employed a descriptive-quantitative approach. The target population comprises MSMEs in Surabaya the sample consists of 100 respondents. Data were collected via questionnaires and subsequently analyzed using SPSS software and multiple linear regression analysis. The results show that Accounting Information Systems, Peer-to-Peer Lending (P2P), and Payment Gateways partially have a positive effect on the financial performance of MSMEs in Surabaya. This indicates that the implementation of accounting information systems and the optimal use of financial technology can help MSME players improve the effectiveness of financial management, facilitate access to capital, and support smooth business transactions, thereby improving financial performance.